Modes of Entry to Male Immigrant Entrepreneurship in a Rural Context: Start-up Stories from Northern Norway - Mai Camilla Munkejord (Entrepreneurial Business and Economics Review, 2016)
Objective: The purpose of this article is to address rural and gender gaps in the immigrant entrepreneurship literature by analysing the start-up narratives of nine male entrepreneurs in Finnmark in northernmost Norway. Research Design & Methods: The article is based on a qualitative fieldwork including business visits and in-depth interviews. The transcripts from the interviews were analysed using a constructivist grounded theory approach (CGT). Findings: The article contributes to the entrepreneurship literature in general and to the immigrant entrepreneurship literature in particular in three ways: first, by high-lighting the gendered experiences of male immigrant entrepreneurs; second, by identifying three distinct modes of entry into rural immigrant entrepreneurship, including a) entrepreneurship as a means to live in a region of perceived attractiveness; b) entrepreneurship ‘because I was asked to do it’ and c) entrepreneurship as a preferred choice for men in satisfactory wage labour; and third, by revealing that the experiences of participants, regardless of their mode of entry into entrepreneurship, are shaped by the family and spatial contexts in which the entrepreneurs are situated. Implications & Recommendations: This study notes that the modes of entry to rural immigrant entrepreneurship are diverse, but often related to the pursuit of an initial feeling of belonging in the new region of settlement. Hence, developing our knowledge of how to not only attract but also retain and increase the feeling of local belonging of immigrants may be important for many rural regions in the Western world. This is because rural immigrants not only represent a much needed inflow of younger people in a typically decreasing and ageing population, but also entail cultural variation and job creation, thus contributing to place development. Contribution & Value Added: The originality of this article is to address rural and gender gaps in the immigrant entrepreneurship literature by analysing the start-up ...